ANALYSIS OF EARLY CHILDHOOD ACTIVITY DEVELOPMENT IN THE AN NISA PLAYGROUP - Setiawan, Devi Sylvia; Nurhayati, Sri (IKIP Siliwangi Bandung, 2025)
This study aims to determine the development of early childhood activities in the Annisa play group. The research subjects were the Anisa Playgroup students. The method used in this study is a descriptive research method and interprets data regarding the phenomena/symptoms studied in the field. This research data collection technique is through observation, interviews and documentation. The variables analyzed include the program and its implementation in the An- nisa play group which focuses on activities to introduce religious values, through the practice of ablution, practice of prayer as well as memorizing daily prayers. The results of the research and data analysis show that the Annisa Playgroup already has a development program that is implemented in good and directed activities so that it can achieve the expected goals of preparing a generation that is smart, cheerful, has good character and has noble character.